Topiramate pharmacokinetics in neonates undergoing therapeutic hypothermia and proposal of an optimised dosing schedule. (22nd August 2019) - Marques, María Remedios; Garcia‐Robles, Ana; Usach, Iris; Vento, Maximo; Poveda, José Luis; Peris, José Esteban; Mangas‐Sanjuan, Victor
Abstract: Aim: The adequate dosing of topiramate in neonates undergoing therapeutic hypothermia has not been established. The aim of this study was to design a dosing schedule capable of providing topiramate serum concentrations within the accepted therapeutic range. Methods: Neonates (n = 52) with hypoxic ischaemic encephalopathy and subjected to therapeutic hypothermia were dosed with topiramate, 5 mg/kg on day one and 3 mg/kg on days two to five, to decrease seizure events. A total of 451 topiramate serum concentrations obtained in the patients were used to develop a population pharmacokinetic model using a non‐linear mixed‐effects modelling approach. Results: A one‐compartment model with first‐order absorption and two different clearance terms, one for the cooling period and another for the post‐warming period, were used to describe the concentration‐time topiramate data. The probability of no‐seizure events could not be related to topiramate concentrations, which was attributed to excessively low topiramate concentrations. A modified dosage schedule was designed with the aim of obtaining more than 90% of patients with topiramate concentrations within the therapeutic range after the first dose. Conclusion: The dosage schedule of topiramate in these patients should be modified with the aim of decreasing the frequency of seizure events.